1981
DOI: 10.1007/bf00410117
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte interferon in therapy of patients with urinary bladder papillomatosis, breast cancer, and melanoma

Abstract: The authors report the result of local and parenteral applications of human leukocyte crude interferon in the therapy of eight patients with urinary bladder papillomatosis, four patients with breast cancer, and two patients with melanoma. The doses and effects of treatment are presented in tables. Clinical application of human leukocyte interferon (HLI) to these three types of malignant tumors has yielded encouraging results. The authors believe that investigations on HLI applications to some malignant tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The use of interferon for HPV-related diseases was actually begun before DNA hybridization studies confirmed virus involvement, Clinical investigations of crude human leukocyte interferon (HLI) were conducted at the Institute of Immunology in Zagreb, Yugoslavia, in the 1970's (28)(29)(30)(31)(32). Early clinical trials involved the treatment of some malignant tumors, including invasive squamous cell carcinoma and precancerous states of the uterine cervix.…”
Section: History Of Interferon Usage Early Milestonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of interferon for HPV-related diseases was actually begun before DNA hybridization studies confirmed virus involvement, Clinical investigations of crude human leukocyte interferon (HLI) were conducted at the Institute of Immunology in Zagreb, Yugoslavia, in the 1970's (28)(29)(30)(31)(32). Early clinical trials involved the treatment of some malignant tumors, including invasive squamous cell carcinoma and precancerous states of the uterine cervix.…”
Section: History Of Interferon Usage Early Milestonesmentioning
confidence: 99%
“…No pathologic progression was detected during the two year period of observation. In contrast, the lesions of control patients demonstrated malignant progression (30,31), Cancer studies were organized into three phases. In Phase I, intralesional injections were administered to 10 patients with cervical cancer and changes were monitored cytologically and histologically (32).…”
Section: History Of Interferon Usage Early Milestonesmentioning
confidence: 99%